A vivo study on dowel crown with more aesthetic and healthy Fiber Reinforced Composite post system - Hasan, Hasibul; Rahman, Kasi Hasinur; Sultana, Shamim; Rahman, Md Mahfuzur; Alam, Md Shasul (City Dental College Journal, 2012)
Statement of problem. Patients having grossly carious teeth with broken down crown are needed to be restored with post & core after endodontic treatment. Root canal posts are widely used & come in a variety of metals & forms. However, cast metal posts, although better than other post & core systems, still possess some disadvantages, like corrosion & discoloration at the gingival margin of the treated tooth & cause aesthetic problem. These problems are overcome with the recently introduced post & core material. The fiber reinforced composite post & core material is a superior & efficient alternative to cast post. Purpose. The purpose of this study was to investigate the success of fiber reinforced composite post & core system over conventional metallic system in regards of corrosion & discoloration resistance with periodontal condition on post treated tooth. Materials & Methods. This was a prospective study, conducted in the department of Conservative Dentistry & Endodontics, B.S.M.M.U. 40 patients were purposively selected who attended in this department with grossly carious teeth with badly broken crown without apical infection as the subject of this study & divided in two groups. 20 patients were included in group A as case subjects & they were treated with fiber reinforced post & core system. 20 patients were included in group B as control subjects. They were treated with conventional cast metallic post & core system. After twelve months, recorded data were compiled on a master chart and statistically analyzed. Chisquare test and t-test (unpaired) were done for statistical significance (P<0.05). Results. Very highly significant difference (p<.001) was observed between the groups in the evaluation of resistance to corrosion & discoloration, there were no significant difference (p>.05) in periodontal evaluation Conclusion. This study revealed that fiber reinforced composite post & core system can overcome the problems faced by the metallic post & core system. So it can be concluded that fiber reinforced composite post & core system can be a promising alternative in comparison to metallic post & core system. DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11832 City Dental College Journal Vol.9(1) 2012 15-18